MAKNA BODY SHAMING PADA FILM 200 POUNDS BEAUTY VERSI INDONESIA (ANALISIS SEMIOTIKA CHARLES SANDERS PEIRCE) - Lila Sari Andamaya; Iin Soraya; Yogi Ariska (An Nafi': Multidisciplinary Science, 2025)
The phenomenon of body shaming remains widespread in Indonesian society and is often considered normal as a form of humor, even though it has serious psychological impacts on victims. Film, as a medium of mass communication, can represent this phenomenon through scenes, dialogues, and visual symbols. This study aims to examine the meaning of body shaming in the Indonesian version of 200 Pounds Beauty using Charles Sanders Peirce’s semiotic theory. The research employs a descriptive qualitative method with a constructivist paradigm. Data were collected through observation, documentation, and literature review. From 48 observed scenes, 10 scenes containing signs of body shaming were selected for further analysis. The analysis shows that body shaming in the film encompasses five elements: social cognition, self-evaluation, emotional, behavioral, and psychological. The findings highlight that the film not only reflects narrow beauty standards but also illustrates the profound social and psychological impacts experienced by victims of body shaming.